Antisera production against the somatic (O) antigen of Escherichia coli O157 H7 - Acosta, Michael Pablo; Azanza, Ma. Patricia V. (2005)
ABSTRACT The study focused on producing an antisera specific for the O157 antigen of Escherichia coli O157:H7 by immunizing BALB/c mice and New Zealand white rabbit with an antigenic material using methods designed to isolate fimbrial extract of E. coli O157:H7. Fractions containing 90 kilodaltons (kDa) protein subunit evaluated by SDS-PAGE were concentrated and used as the immunizing antigen. The results of the study indicated possible isolation of outer membrane proteins of somatic antigens other than the expected fimbrial protein components. Evaluation of antisera produced by the test animals was done through Immunodot, Westrnblot, and sandwhich ELISA (sELISA). The Immunodot has shown that the immunized animals produced polyclonal antibodies against the immunized antigen. For the Westernblot test, the partially purified antigen produced 3 bands with molecular weights 118, 97, and 63 kDA. The study hypothesized that the bands possibly could be lipopolysaccharide complexes (somatic/O antigens) associated with the protein fraction. The vegetative cells of E. coli O157:H7 were found to be more reactive to an sELISA technique using mouse antisera as capture antibody and rabbit antisera as capture antibody and rabbit antisera as detecting antibody, relative to the 9 gram-negative bacteria, except for S. marscesens. Possible similarities in O antigens of E. coli O157:H7 and S. marscesens was used to explain the result. Because of the lack of specificity of the produced antisera, the study recommended focusing on the enhancement of purification techniques by including steps such as the use of detergent, chromatographic techniques and electron microscopy.
Thesis (BSFT)--University of the Philippines, Diliman
Keywords: Immune serums; Escherichia coli